Southern pudu (Pudu puda) (Artiodactyla: Cervidae) as an additional host for Dictyocaulus eckerti (Strongylida: Dictyocaulidae) - Pablo Oyarzún-Ruiz; Pamela Muñoz; Gastón Valenzuela (Revista Mexicana de Biodiversidad)
Southern pudu (Pudu puda Molina, 1782) is the most austral native deer in South America, being distributed in Chile and Argentina, countries where it has conservation issues. Seven lungworms were isolated from the bronchi of one southern pudu from Los Ríos region. Such helminths were identified as adult females and males of Dictyocaulus eckerti Skrjabin, 1931, a lungworm isolated in wild and domestic deers from Europe, New Zealand and North America. There are previous reports of unidentified species of Dictyocaulus in P. puda from Southern Chile. However, this is the first record of P. puda acting as a natural host of D. eckerti. Due to the establishment of wild populations of European deers in Southern Chile, sharing grazing places between native and exotic deers could allow for the transmission of such parasites. Thus, the present report highlights the potential additional impact of exotic mammals over this threatened deer.